Diachronic Corpora as a Tool for Tracing Etymological Information of Indonesian-Malay Lexicon - Kamal Yusuf; Dewi Puspita (UIN Salatiga, 2020)
Indonesian lexicon comprises numerous loanwords which some of them already exist since the 7th century. The large number of loanwords is the reason why many dictionaries of Indonesian etymology available today contain merely the origin of the words. Meanwhile, there are several aspects in a word etymology that can be studied and presented in a dictionary, such as the change in a word form and in its meaning. This article seeks to demonstrate the use of corpora in identifying the etymological information of Malay words from diachronic corpora and to figure out the semantic change of the Malay words undergo from time to time until they turn out to be Indonesian lexicon. More specifically, two selected Malay words were examined: bersiram and peraduan. By exploring data resources from the corpus of Malay Concordance Project and Leipzig Corpora, this study attempts to collect etymological information of Indonesian lexicon originated from Malay by employing a corpus based research. The findings show that the examined words have changed in meaning through generalization and metaphor. However, unlike the word bersiram, the change that the word peraduan happened only occurs in semantic level. This information, ultimately, can be used as informative data for a more comprehensive Indonesian etymology dictionary. Drawing on corpus analysis, this paper addresses the importance use of diachronic corpora in tracing words origin.Keywords: diachronic corpora, etymology, corpus analysis, semantic change, Malay-Indonesian